Emotional intelligence and digital skills in the perception of employability in young university students who enter the labor market - García Selva , Adrián; Deltell Amorós , Jessica; Pons Ferrández, Inmaculada Concepción; Solanes Puchol, Ángel; Martín del Río , Beatriz (Conferência - Investigação e Intervenção em Recursos Humanos, 2023)
The Spanish economy has an average unemployment rate of close to 40% in people under 29 years of age with higher education, a fact that has led us to investigate what other elements in addition to university education are necessary for this group to achieve job placement. The literature shows that there are other skills with a higher level of importance that today are essential to acquire a job. Currently, digital skills and emotional intelligence are two of the most demanded hard and soft skills, respectively (Lyu & Liu, 2021). This study analyzes the emotional intelligence and digital skills that young university students possess in relation to their perception of employability. 111 people participated in the study, 33 men (29.7%) and 78 women (70.3%). The age range oscillated between 21 and 30 years, with a mean of 24.7 (SD = 2.05). Regarding the distribution by disciplines, 79 (71.2%) people studied branches of Social and Legal Sciences, while 6 (5.4%) studied Arts and Humanities, 9 (8%) studied Experimental Sciences, 6 (5.4%) studied Engineering and Architectures, and 11 (10%) studied disciplines related to Health Sciences. Variables and instruments The perception of employability was evaluated using the Perception of Employability Scale in university students (Hernández-Fernaud et al., 2011). On the other hand, emotional intelligence was measured using the reduced version of the Emotional Meta-knowledge Trait Scale (TMMS-24), developed by Salovey et al. (1995) and adapted by Fernández et al. (2004). This questionnaire is made up of three dimensions: 1) attention; 2) clarity; and 3) repair. Regarding digital skills, this variable was evaluated with the questionnaire prepared by Conde-Jiménez (2017), which is made up of 7 factors: 1) basic skills of knowledge and use of the computer and the Internet; 2) participation and collaboration through the network; 3) resource and content creation skills; 4) digital awareness; 5) use of devices as tools and resources; 6) ethics in the digital environment; and 7) access and use of digital platforms. Statistical analysis. Spearman correlation analysis, ANOVA and T test (95% confidence level). Analyzes were performed with SPSS 26. Results: Firstly, a Spearman correlation analysis has been carried out between emotional intelligence and perception of employability, and between digital skills and perception of employability. Only the dimensions of clarity (rs = .33, p = .006) and repair (rs = .26, p = .002) of emotional intelligence have obtained a significant relationship with the perception of employability. On the other hand, only the dimensions of participation and collaboration through the network (rs = .19, p = .049), resource and content creation skills (rs = .21, p = .029) and ethics in the digital environment (rs = .19, p = .041) of digital skills are positively and significantly related to the perception of employability. Several ANOVAs were carried out. First, three groups were created based on the cut-off points of the emotional intelligence questionnaire (low, medium, and high scores). The ANOVAs reflect that there are significant differences in the perception of employability based on the dimension of clarity (F2, 108 = 4.75, p = .011) and the dimension of repair (F2, 108 = 3.48, p = .034) of intelligence emotional. Specifically, these differences occur between the low-score and high-score groups, with a moderate effect size for the clarity dimension (ω2 = .06) and a slight one for the repair dimension (ω2 = .04). Finally, two groups with medium and high scores in digital skills were created. In this case, the T test shows that there are significant differences in the perception of employability based on the total digital skills score (t.95; 33 = -3.095; p = .003). However, the Cohen's delta value obtained is .06, indicating a small effect size. Discussion: Based on what was obtained, it can be anticipated that if young people develop their emotional intelligence and digital knowledge, the perception of employability will improve, and performance and success in a job may be greater (García, 2017; Yorke, 2006; Zeidner et al., 2004). This study reflects that emotional intelligence has a great impact on the perception of youth employability, as well as digital skills, although to a lesser extent.